The mechanical behavior of silk-fibroin reinforced alginate hydrogel biocomposites - Toward functional tissue biomimetics. (February 2023) - Aharonov, Adi; Mordechai, Haim S.; Sharon, Smadar E.; Sharabi, Mirit
Abstract: Soft tissues are constructed as fiber-reinforced composites consisting of structural mechanisms and unique mechanical behavior. Biomimetics of their mechanical behavior is currently a significant bioengineering challenge, emphasizing the need to replicate structural and mechanical mechanisms into novel biocomposite designs. Here we present a novel silk-based biocomposite laminate constructed from long natural silk and fibroin fibers embedded in an alginate hydrogel matrix. Controlling the mechanical features of these laminates were studied for different fiber volume fractions (VF) and orientations using unidirectional tensile tests. Three material systems were investigated having different fiber orientations: longitudinal (0°), transverse (90°), and cross-plied (0/90°). The general behavior of the biocomposite laminates was anisotropic hyperelastic with large deformations. Longitudinal fibroin laminates have shown a tensile modulus of 178.55 ± 14.46 MPa and tensile strength of 18.47 ± 2.01 MPa for 0.48 VF. With similar VF, cross-plied fibroin laminates demonstrated structural shielding ability, having a tensile modulus and tensile strength of 101.73 ± 8.04 MPa and 8.29 ± 1.63 MPa for only a third of the VF directed in the stretching direction. The stress-strain behavior was in a similar range to highly stiff native human soft tissues such as ligament and meniscus. These findings demonstrate the potential of the fibroin fiber-reinforced biocomposites to mimic the mechanics of tissues with a quantitatively controlled amount of fibers and designed spatial arrangement. This can lead to new solutions for the repair and replacement of damaged functional and highly stiff soft tissues.